Предмет: Алгебра, автор: stroeva2005nata

Решите уравнение (X²-7x+8)(x²+9x+8)=-39x²

Ответы

Автор ответа: Miа16
0

Ответ:

(x^2-7x+8)*(x^2+9x+8)=-39x^2

x^4+9x^3+8x^2-7x^3-63x^2-56x+8x^2+72x+64=-39x^2

x^4+2x^3-47x^2+16x+64=-39x^2

x^4+2x^3-47x^2+16x+64+39x^2=0

x^4+2x^3-8x^2-16x+32x+64=0

x^3*(x+2)-8x*(x+2)+32(x+2)=0

(x+2)*(x^3-8x+32)=0

(x+2)*(x^3-16x+8x+32)=0

(x+2)*(x*(x^2-16)+8(x+4))=0

(x+2)*(x*(x-4)*(x+4)+8(x+4))=0

(x+2)*(x+4)*(x*(x-4)+8)=0

(x+2)*(x+4)*(x^2-4x+8)=0

x+2=0

x+4=0

x^2-4x+8=0

x₁= -4, x₂ = -2

Объяснение:

Автор ответа: palilov243659
0

Ответ:

Объяснение:

///////////////////////////////////////

Приложения:
Похожие вопросы